(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the history of scientific intelligentsia of Naddnipryanscaya Ukraine. In it is devoted participation representatives scientific intelligentsia in cultural and education work and in process popularization of scientific knowledge among population of Ukraine in the second half of XIX ñ beginning of the XX centuries.